Increased fibroblast chymase production mediates procollagen autophagic digestion in volume overload. (March 2016) - Fu, Lianwu; Wei, Chih-Chang; Powell, Pamela C.; Bradley, Wayne E.; Ahmad, Sarfaraz; Ferrario, Carlos M.; Collawn, James F.; Dell'Italia, Louis J.
Abstract: Background: Previous work has identified mast cells as the major source of chymase largely associated with a profibrotic phenotype. We recently reported increased fibroblast autophagic procollagen degradation in a rat model of pure volume overload (VO). Here we demonstrate a connection between increased fibroblast chymase production and autophagic digestion of procollagen in the pure VO of aortocaval fistula (ACF) in the rat. Methods and results: Isolated LV fibroblasts taken from 4 and 12 week ACF Sprague–Dawley rats have significant increases in chymase mRNA and chymase activity. Increased intracellular chymase protein is documented by immunocytochemistry in the ACF fibroblasts compared to cells obtained from age-matched sham rats. To implicate VO as a stimulus for chymase production, we show that isolated adult rat LV fibroblasts subjected to 24 h of 20% cyclical stretch induces chymase mRNA and protein production. Exogenous chymase treatment of control isolated adult cardiac fibroblasts demonstrates that chymase is internalized through a dynamin-dependent mechanism. Chymase treatment leads to an increased formation of autophagic vacuoles, LC3-II production, autophagic flux, resulting in increased procollagen degradation. Chymase inhibitor treatment reduces cyclical stretch-induced autophagy in isolated cardiac fibroblasts, demonstrating chymase's role in autophagy induction. Conclusion: In a pure VO model, chymase produced in adult cardiac fibroblasts leads to autophagic degradation of newly synthesized intracellular procollagen I, suggesting a new role of chymase in extracellular matrix degradation. Highlights: Volume overload induces chymase production in cardiac fibroblasts isolated from 4- and 12-week aortocaval fistula rats. Exogenous chymase enters cardiac fibroblasts in a dynamin-dependent manner. Chymase treatment of adult cardiac fibroblasts leads to increased autophagic flux and procollagen degradation. Autophagy associated with increased chymase after stretch of cardiac fibroblasts is attenuated by chymase inhibitor.